TOOL BASED ON KNOWLEDGE MANAGEMENT PROCESS: AN INTERVIEW PROTOCOL TO GATHER FUNCTIONAL REQUIREMENTS FROM SOFTWARE INDUSTRY EXPERTS - Tenório, Nelson; Pinto, Danieli; Vidotti, Amanda Ferrarezi; Oliveira, Mariana Santos; Urbano, Gisele Caroline; Bortolozzi, Flávio (MATTER: International Journal of Science and Technology, 2017)
The company's knowledge is composed of different individual pieces of knowledge. In the software industry, the individuals use personal technologies to communicate to each other project issues, which generate a part of the organizational knowledge. However, using those tools in that manner, the software industry faces the knowledge fragmentation problem. It creates difficulty in utilizing Knowledge Management processes (e.g. capture, store, and recover) in their decision-making. Thus, this research proposes an interview protocol to gather functional requirements from software industry experts. The interview protocol is based on a literature review regarding Knowledge Management processes and tools over the past years. The result achieved in this paper is an interview protocol guided by knowledge management process validated by twelve experts.